2021
DOI: 10.1371/journal.pone.0256380
|View full text |Cite
|
Sign up to set email alerts
|

Machine learning for manually-measured water quality prediction in fish farming

Abstract: Monitoring variables such as dissolved oxygen, pH, and pond temperature is a key aspect of high-quality fish farming. Machine learning (ML) techniques have been proposed to model the dynamics of such variables to improve the fish farmer’s decision-making. Most of the research on ML in aquaculture has focused on scenarios where devices for real-time data acquisition, storage, and remote monitoring are available, making it easy to develop accurate ML techniques. However, fish farmers do not necessarily have acce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 22 publications
0
11
0
Order By: Relevance
“…The reported studies (Kokol et al, 2022; Vabalas et al, 2019) indicate the availability of ML techniques in the validation of limited data as in our study. Furthermore, the reported results showed the possibility of achievement of successful results with ML by using limited data (Zambrano et al, 2021).…”
Section: Resultsmentioning
confidence: 99%
“…The reported studies (Kokol et al, 2022; Vabalas et al, 2019) indicate the availability of ML techniques in the validation of limited data as in our study. Furthermore, the reported results showed the possibility of achievement of successful results with ML by using limited data (Zambrano et al, 2021).…”
Section: Resultsmentioning
confidence: 99%
“…Random Forests for forecasting water quality variables such as dissolved oxygen, pond temperature, etc. [110] RMSE for pond temperature = 0.5971, RMSE for dissolved oxygen = 1.616.…”
Section: Big Data and Artificial Intelligencementioning
confidence: 97%
“…Both classifiers provided an average accuracy of 100% during the training phase and average of 99.45% during the testing phase. Zambrano et al [110] propose the use of machine learning tools to forecast water quality variables such as dissolved oxygen, pH, and pond temperature. A comparison is performed between Random Forests (RF), ANNs, and multivariate linear regression, out of which RFs performed the best.…”
Section: Big Data and Artificial Intelligencementioning
confidence: 99%
“…In fsh farming, Zambrano et al [23] introduced an ML model for manually observed water quality prediction. In cases where the number of measurements was restricted, the author used RF, MLR, and ANN to assess data from water quality indicators that are regularly recorded in fsh growth and farming.…”
Section: Related Workmentioning
confidence: 99%